Separatism Movement and Contemporary Reconciliation: Causes and its Impact towards Political Development in Papua - Reni Rentika Waty; Ibrahim Mifthafariz Mirza; Najmi Muhammad Fadli (Jurnal Studi Sosial dan Politik, 2022)
The separatism occurs in Papua that comes from the root of complex problems, resulting in ongoing conflict between the Free Papua Organization (OPM) and the state. Separatism and conflict in Papua have had a significant impact on political development. This research uses Tedd Robert Gurr's theory of relative deprivation and Lucian Pye's theory of political development as well as qualitative methods. This research examines conflicts and separatism that occur in Papua and their relation to Papuan political development. The result of this research indicates that political development in Papua has not been successful. The discrepancy between expectations for progress and realities can lead to significant political violence. The strengthening of collective discontent can be politicized and produce radical and even separatist resistance movements. These conditions can hinder the course of the political development process, because of the difficulty of building integration and creating political stability.